Оценка состояния питания и пищевого статуса детей раннего возраста южного региона = Assessment of the nutrition status of infants in South region - V. I. Velichko; G. A. Danilchuk; L. I. Kolotvin; A. V. Chernetskaya (Kazimierz Wielki University, 2017)
Velichko V. I., Danilchuk G. A., Kolotvin L. I., Chernetskaya A. V. Оценка состояния питания и пищевого статуса детей раннего возраста южного региона = Assessment of the nutrition status of infants in South region. Journal of Education, Health and Sport. 2016;6(11):548-556. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192832 http://ojs.ukw.edu.pl/index.php/johs/article/view/4042         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016.   ОЦЕНКА СОСТОЯНИЯ ПИТАНИЯ И ПИЩЕВОГО СТАТУСА ДЕТЕЙ РАННЕГО ВОЗРАСТА ЮЖНОГО РЕГИОНА   В. И. Величко, Г. А. Данильчук, Л. И. Колотвина, А. В. Чернецкая   Одесский национальный медицинский университет   Резюме. Актуальность. Разбалансированное питание в раннем детском возрасте нередко приводит к нарушению состояния здоровья ребенка, в том числе к задержке психического развития, нарушению механизмов адаптации и снижению иммунологической защиты. Изучение и оценка фактического питания детей раннего возраста и его влияния на здоровье и развитие младенцев позволит разработать необходимые рекомендации как для родителей, так и для врачей. Цель исследования: изучить распространенность грудного вскармливания среди детей грудного возраста, проживающих в южных регионах Украины (Одесской, Николаевской и Херсонской областях). Результаты. Проведен комплексный анализ фактического питания детей раннего возраста, получены данные о сроках прикладывания ребенка к груди и докармливании смесями в роддоме, продолжительности грудного вскармливания, частоте включения в питание кормящей матери и ребенка цельного коровьего молока и молочных продуктов. Выводы. Установлено, что распространенность грудного вскармливания остается недостаточной, отмечается недостаточная осведомленность женщин о принципах грудного вскармливания, 33,8% детей докармливаются смесью в родильном доме. Ключевые слова: дети в возрасте 0-12 мес, фактическое питание, режим питания, продолжительность грудного вскармливания.   ASSESSMENT OF THE NUTRITION STATUS OF INFANTS IN SOUTH REGION   V. I. Velichko, G. A. Danilchuk, L. I. Kolotvin, A. V. Chernetskaya   Odessa National Medical University Abstract Relevance. Unbalanced nutrition in early childhood often leads to disruption of the state of children's health, including mental retardation, disturbance of the mechanisms of adaptation and reduction of immunological protection. The study and evaluation of actual nutrition of infants and its impact on the health and development of infants will develop the necessary guidance for parents and for doctors. Objective: to study the prevalence of breastfeeding among infants living in the southern regions of Ukraine (Odessa, Nikolaev and Kherson regions). Results. The complex analysis of actual nutrition of young children, the data on the timing of applying the child to her breast and supplemental foods mixtures in hospital, duration of breastfeeding, the frequency of inclusion in the nutrition nursing mother and baby cow's milk and dairy products. Conclusions. It was found that the prevalence of breastfeeding is insufficient, there is a lack of awareness of the principles of women breastfeeding, 33.8% of children finish feeding mixture in the maternity hospital.  Key words: children aged 0-12 months, the actual nutrition, diet, duration of breastfeeding.